Tandem Deoxygenative Geminal Fluorosulfonimidation of 1,2-Diketones via Formal N–F Insertion Enabled by Dealkylation-Resistant Phosphoramidite - Bak, Sujin; Son, Yeri; Hwang, Sunjoo; Kim, Ha Eun; Choi, Jun-Ho; Chung, Won-jin (Synthesis, 2023)
Our group has recently developed an α-fluoroamine synthesis using dioxaphospholenes derived from various 1,2-diketones and the dealkylation-resistant phosphoramidite as carbene surrogates, enabling the formal insertion into the N–F bond of (PhSO2)2NF. This full account presents the scope and limitations in terms of the reactivity and the site selectivity; these were rationalized through computational analysis. In addition, the efforts to broaden the synthetic utility of the current process by incorporating other nitrogen nucleophiles and halogen electrophiles are described.
Keywords: fluoroamine; sulfonimide; dioxaphospholene; carbene surrogate; phosphoramidite; N–F insertion; geminal difunctionalization; 1,2-diketone